Study of fast frequency-hopped multiple access systems - Li, Chenlu (2018)
Frequency hopping communication technology has the characteristics of strong anti-interference ability, high frequency spectrum utilization rate, good confidentiality, anti - multipath, anti - fading, easy networking and so on. At present, frequency hopping technology is not only mainly used in the field of military communications, but also widely used in civil areas, such as mobile communications, radar, navigation, wireless local area network, etc. This dissertation mainly studies the design, implementation and simulation of fast frequency hopping multiple access system (FFH/MA). MATLAB is used to simulate the BER performance of binary frequency-shift keying (BFSK) signal in FFH/MA system. The effects of multiple users, noise, different fading channels, different diversity levels and different diversity-combining techniques on BER are studied. The optimal structure of the system under different conditions is analyzed. Finally, all the different situations are compared and summarized.